Response of Onion, T. Aus and T. Aman Rice to NPKS Fertilizers in the High Ganges River Floodplain Soil (Progressive Agriculture, 2013)
An experiment was conducted at farmers field of Kushtia sadar MLT site under AEZ 11 during three consecutive years at 2001-2004 to find out the rate of nutrients (NPKS) for Onion (Taherpuri), T. aus (IR-50) and T. aman rice (BR-11) to NPKS on the yield under AEZ11. Four different levels of NPKS were assigned in RCB design with 4 replications. Average of three years study reveals that a considerable response of Onion, T. aus and T. aman rice to NPKS was observed. However, the response to P, K and S was more distinct in comparison to N. Similarly, the response was more evident in Onion compared with T. aus and T. aman rice. Yield of Onion increased up to the application of 120, 43, 120 and 20 kg/ha of N, P, K and S, respectively. Yield of T. aus and T. aman rice increased up to the application of 70, 18, 34 and 10 kg/ha of N, P, K and S, respectively. From the regression analysis it was found that the relationship was almost quadratic in nature. The application of 115-40-118-18 kg NPKS/ha for Onion, 63-19-29-9 kg NPKS/ha for T. aus rice and 65-17-33-9 kg NPKS/ha for T. aman rice was the most economically optimum fertilizer dose in the High Ganges River Floodplain Soil under AEZ 11.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16851 Progress. Agric. 20(1 & 2): 63 72, 2009